Physical assessment of youth ski jumpers. - Nicholson, Anna (My University, 2007)
The purpose of this study was evaluate the fitness levels of Eau Claire Area youth ski jumpers and to aid the coach in designing individualized training programs to optimize each athlete’s performance and, subsequently, to determine which fitness parameters best correlate with success on the ski jumping hills.
Color poster with text describing research conducted by Anna Nicholson under the supervision of Don Bredle.
Keywords: Physical fitness--Testing.; Physical fitness for youth--Testing.; Child athletes--Training of.; Teenage athletes--Training of.; Ski jumpers--Training of.; Posters.